Pattern of Pediatric Eye Diseases - Ahmad Hussain Klasra, Munawer Ali, Soufia Farrukh, Muhammad Abidl Atif (Pakistan Journal of Ophthalmology, 2015)
Purpose: To assess the pattern of common eye diseases in pediatric population of Bahawalpur. Material and Methods: Total 1000 children coming to outpatient Department of Ophthalmology, Bahawal Victoria Hospital Bahawalpur over a period of two months from 1st June 2014 to 31st July 2014, with age ? 16 years were included in this study. Results: Mean age of the patients was 9.51 ± 4.8 years. Out of 1000 patients 483 (48.3%) patients were males and 517 (51.7%) patients were females. Most of the patients 455 (45.5%) belonged to age group 9-12 years. Most common disorder was refractive errors 322 (32.2%) followed by congenital cataract 231 (23.1%), VKC 219 (21.9%) and squint 124 (12.4%). Conclusion: Male and female children were almost equally affected with ocular disorder and refractive error was the most common disorder in this study. Key Words: Ophthalmology, consanguineous marriages, congenital, childhood blindness, refractive errors.